Assessing news contagion in finance - Paola Cerchiello; Giancarlo Nicola (Econometrics, 2018)
The analysis of news in the financial context has gained a prominent interest in the last years. This is because of the possible predictive power of such content especially in terms of associated sentiment/mood. In this paper, we focus on a specific aspect of financial news analysis: how the covered topics modify according to space and time dimensions. To this purpose, we employ a modified version of topic model LDA, the so-called Structural Topic Model (STM), that takes into account covariates as well. Our aim is to study the possible evolution of topics extracted from two well known news archive-Reuters and Bloomberg-and to investigate a causal effect in the diffusion of the news by means of a Granger causality test. Our results show that both the temporal dynamics and the spatial differentiation matter in the news contagion.
Keywords: C83; C12; E58; E61; G02; G14; 330; behavioural finance; financial news; structural topic model; granger causality